HUBUNGAN PENGETAHUAN SUAMI DENGAN PEMERIKSAAN ANTENATAL CARE (ANC) PADA IBU HAMIL TRIMESTER IIIDI BPS LENNY AM.KEB KECAMATAN PANGKALAN KURAS TAHUN 2018 - Ekry Binti Farizal (STIKES HUSADA GEMILANG, 2019)
Antenatal Care (ANC) is the examination and surveillance on gestation to boost the mental and physical health of pregnant women, so that they are able to have labor, childbirth, breastfeeding preparation, and to repatriate reproductive health naturally. The examination is periodically carried out, weekly examination, to ensure the distortion on pregnant women in order to preserve the mothers and the fetus healthy. The research purposes on finding the correlation between husband knowledge and antenatal care (ANC) on the 3rd trimester pregnant women at BPS Lenny Am.Keb., Pangkalan Kuras Sub-district in 2018. The type of the research was cross-sectional quantitative design. The research was conducted at BPS Lenny Am.Keb., Pangkalan Kuras Sub-district, in which population were 176 people, and it used accidental sampling technique and univariate and bivariate data analysis. Based on the Chi square test, it is found that there is a significant correlation between husband knowledge and antenatal care (ANC) at BPS Lenny Am.Keb., Pangkalan Kuras Sub-district (p value = 0,046). The husband knowledge corresponds to antenatal care (ANC) on the 3rd trimester pregnant women at BPS Lenny Am.Keb., Pangkalan Kuras Sub-district.